ANALISIS PRINSIP MENGENALI PEMILIK MANFAAT UNTUK PENCEGAHAN SERTA PEMBERANTASAN TINDAK PIDANA PENCUCIAN UANG DAN TERORISME - Pancratius Rio Mayrolla; I Gusti Nyoman Yonatan Wiradi; Simbolon, Yolanda (Penerbit Universitas Atma Jaya Yogyakarta, 2023)
The development of economic crimes, particularly regarding money laundering and terrorism financing, led to the promulgation of Law Number 8 of 2010 on Prevention of the Crime of Money Laundering and Law Number 9 of 2013 Regarding Prevention and Eradication of Terrorism Financing Crime. The mode of the crime of the two types of crime also then uses the corporation to disguise it. Presidential Regulation Number 13 of 2018 regarding the application of the Know-Your-Beneficial-Owner Principle by Corporations for the Prevention and Eradication of the Criminal Acts of Money Laundering and Terrorism Financing was promulgated to tackle money laundering and terrorism financing using Corporations. There is an unclear basis for the authority to enact that Presidential Regulation and there is a discrepancy between the criteria for Beneficiary Owners causing legal uncertainty. This study aims to find out and examine the fulfillment of the principle of forming statutory regulations which form the principle of recognizing Beneficiary Owners and to find out and study the determination of Beneficiary criteria in that Presidential Regulation in terms of Law on Prevention of the Crime of Money Laundering and Law Regarding Prevention and Eradication of Terrorism Financing Crime. This study uses normative legal research with a law and regulations approach, where the data obtained is analyzed qualitatively, and the conclusions use a deductive way of thinking. The result of this research is that the principle of recognizing the Beneficiary Owner in that Presidential Regulation is in accordance with the principles of legislation formation; however, the determination of Beneficiary Owner criteria is not accurate.